أسس تسوية مطالبات التأمين البحري دراسة حالة: سوق التأمين السوداني (للفترة 2005 - 2009 م) - موسى علي محمد الحاج عبد الله; عبد العزيز برعي عثمان الشريف (Journal of Economics and Administrative Sciences, 2018)
This research reviews the basis for the settlement of claims when marine losses occur, including the settlement of claims in the case of joint maritime losses for goods and ship objects, as well as the settlement of claims for damage to vessel objects when they are at sea risk and loss during the sea voyage. Construction The Research used descriptive, analytical and historical methods in preparing the research; the society of study composed of the employee in the insurance companies working in Sudan, the questionnaire was distributed for all study samples. The study concluded some important results of which it is , there is a weak of awareness, and lack of understanding by the Insured of the conditions and exceptions of the Marine Insurance Documents and the conditions of the Institute of Marine Insurance Subscribers in London (a), (b) and (c), leading to the occurrence of the dispute between the Insured and the Insurance Companies when settling claims and friendly settlements for marine insurance claims avoid insurers many problems and disputes with the insured. The most important recommendations were resolving disputes over the settlement of marine insurance claims through the courts adversely affects the trust of the insured in the credibility of the company to fulfill its obligation to pay compensation and friendly settlements of marine insurance claims lead to rapid payment of claims at a time when the insured is most in need of compensation until he is affected by the interruption of his business and loss due to delay.